2019
DOI: 10.1088/1361-6528/ab19f0
|View full text |Cite
|
Sign up to set email alerts
|

Regioregularity and deposition effect on the physical/chemical properties of polythiophene derivatives films

Abstract: Polythiophene thin films are widely studied for applications in organic electronics. However, some comparisons are still missing, regarding distinct deposition techniques and regioregularity. Here regioregular and regiorandom alkyl-substituted polythiophene derivatives (P3ATs) were deposited on solid substrates using both Langmuir–Blodgett (LB) and Langmuir–Schaefer (LS) techniques. The main goal was to verify the possible influence of the regioregularity as well the deposition technique on their optical, elec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
4
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 48 publications
0
4
0
Order By: Relevance
“…It soon became apparent that assembling molecules for realizing these tasks is by no means straightforward, not only because it is challenging to develop defect-free (at the molecular level) devices but also due to the need to connect the molecular devices with macroscopic components in a real-world application. These difficulties and limitations have not prevented researchers from investigating many aspects of molecular electronics, with 700–800 papers published per year in recent times, some of which involve LB films. The LB technique has been particularly important for molecular electronics of large-area devices. Difficulties concerning the fabrication of the top contact electrodes in LB films in molecular electronics have been addressed, including the top contact electrode in molecular junctions. …”
Section: Lb Films Used In Molecular (Organic) Electronics and Sensorsmentioning
confidence: 99%
“…It soon became apparent that assembling molecules for realizing these tasks is by no means straightforward, not only because it is challenging to develop defect-free (at the molecular level) devices but also due to the need to connect the molecular devices with macroscopic components in a real-world application. These difficulties and limitations have not prevented researchers from investigating many aspects of molecular electronics, with 700–800 papers published per year in recent times, some of which involve LB films. The LB technique has been particularly important for molecular electronics of large-area devices. Difficulties concerning the fabrication of the top contact electrodes in LB films in molecular electronics have been addressed, including the top contact electrode in molecular junctions. …”
Section: Lb Films Used In Molecular (Organic) Electronics and Sensorsmentioning
confidence: 99%
“…, the direct current conductivity (σ dc ) of the LS films of pure and mixed fullerenes can be calculated. Thus, through the slope of the graphs (1/R) and the geometric parameters of the IDE, which in this study is the cell constant (κ), the σ dc values were obtained as shown in the work of Roncaselli et al 24 . The cell constant κ was calculated considering the height of the digits, spacing between them, their number and length using a theoretical model 25 , and for the IDE used in this work this value is 5.1 m − 1 .…”
Section: Resultsmentioning
confidence: 78%
“…electrochemical, electrical, optical, magnetic, thermal, chemical or biological. [16][17][18][19][20][21][22][23][24][25][26][27][28][29] Another strength of PTs is the possibility of obtaining them in diverse physical states [30,31] and configurations/morphologies [32][33][34] through a great variety of well-established synthetic procedures. [35][36][37][38][39][40] In addition to that, the combination of such favourable aspects in PTs can also lead to the realization of new-generation devices in which PTs, in the role of active materials, are designed and configured for possessing dynamic features [41][42][43][44] and accomplishing smart functions.…”
Section: Introductionmentioning
confidence: 99%